Post-flood morbidity and associated factors among flood-affected residents: a cross-sectional study in Dak Lak, Vietnam - Tinh Luu-Viet; Duc Cao-Tien; Nhu-Thao Nguyen-Le; Ngoc-Viet Tran; Duy-Vu Hoang (International Journal of Public Health Science (IJPHS), 2026)
Floods are among the most frequent natural disasters in Vietnam and may substantially affect community health. This study aimed to investigate post-flood diseases and associated risk factors among residents in Dak Lak Province. A community-based cross-sectional study was conducted among 183 adults in Hoa Le and Krong Kmar communes, Dak Lak Province. Participants were recruited using convenience sampling. Data were collected through face-to-face interviews using a structured questionnaire. Multivariable logistic regression was performed to identify factors associated with post-flood morbidity. Overall, 44.3% of participants reported at least one illness during the flood or within three days thereafter. Respiratory diseases were the most common (12.0%), followed by infectious (9.3%), dermatological (8.2%), gastrointestinal (6.6%), and ocular diseases (3.8%). Female sex (OR = 2.52; 95% CI: 1.31-4.83), emergency evacuation (OR = 5.42; 95% CI: 1.41-20.90), and disruption of essential services (OR = 2.06; 95% CI: 1.01-4.18) were significantly associated with post-flood illness. Flooding was associated with substantial morbidity, particularly respiratory and infectious diseases. Strengthening access to safe water, healthcare services, and disease surveillance may help reduce post-flood health risks in affected communities.